FDI spillover effect on the green productivity of Vietnam manufacturing firms: the role of absorptive capacity - Phung Mai Lan; Nguyen Thuy Trang; Nguyen Khac Minh (Journal of Applied Economics)
This study examines the contribution of absorptive capacity to the relationship between FDI spillover effects and firm-level green total factor productivity (GTFP) using the Malmquist-Luenberger productivity index approach combined with a threshold regression model. Using firm-level data from annual enterprise surveys in Vietnam’s manufacturing and processing industries from 2013 to 2019, the study found that absorptive capacity had an important mediating role in amplifying the beneficial effects of FDI spillover. The magnitude of horizontal FDI spillover varies with absorptive capacity in medium high technology (MHT) sectors, while negative effects are observed in medium low technology (MLT) and low technology (LT) sectors. Firms with HT, MLT, and LT sectors have positive backward effects on productivity if their absorptive capacity exceeds a particular threshold. Furthermore, our findings point to specific factors that may be crucial in improving absorptive capacity, such as internal research and development, process improvement, and export.